2015
DOI: 10.15171/ijhpm.2015.171
|View full text |Cite
|
Sign up to set email alerts
|

Rights Language in the Sustainable Development Agenda: Has Right to Health Discourse and Norms Shaped Health Goals?

Abstract: While the right to health is increasingly referenced in Sustainable Development Goal (SDG) discussions, its contribution to global health and development remains subject to considerable debate. This hypothesis explores the potential influence of the right to health on the formulation of health goals in 4 major SDG reports. We analyse these reports through a social constructivist lens which views the use of rights rhetoric as an important indicator of the extent to which a norm is being adopted and/or internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…The issue of universal health coverage (Target 3.8) has been extensively discussed over the last three years 24,25 and has the potential to contribute substantially towards universal access to reproductive health services provided that a rightsbased approach supersedes so-called morality and sociocultural issues 26,27 . The selection of indictors for this target is still in process and will likely not be resolved until late 2016.…”
Section: Target 38 "Achieve Universal Health Coverage Including Finmentioning
confidence: 99%
“…The issue of universal health coverage (Target 3.8) has been extensively discussed over the last three years 24,25 and has the potential to contribute substantially towards universal access to reproductive health services provided that a rightsbased approach supersedes so-called morality and sociocultural issues 26,27 . The selection of indictors for this target is still in process and will likely not be resolved until late 2016.…”
Section: Target 38 "Achieve Universal Health Coverage Including Finmentioning
confidence: 99%
“…1 Their paper speculated about, but was written before the United Nations (UN) adopted the final text of Transforming Our World: the 2030 Agenda for Sustainable Development. 2 We examined Transforming Our World and found it had explicit human rights discourse and health goals that are consistent with right to health entitlements, in particular, universal health coverage.…”
Section: Introductionmentioning
confidence: 99%
“…In fact what the General Assembly adopted as Goal 3 of the SDGs was almost word-for-word the text recommended by the Open Working Group (OWG) in its report of August 2014. 4 Other than a small (but significant) addition to the OWG's proposal for Goal 3.2, indeed, the two texts are identical [1] . The OWG report was one of the four examined by Forman and colleagues, and they found that it was the one with the lowest 'prevalence' of rights-relevant terminology [2] , including "no explicit reference to the right to health or to sexual and reproductive health rights. "…”
mentioning
confidence: 96%
“…n their hypothesis published in IJHPM in December 2015, 1 Lisa Forman and colleagues examined the prominence of the right to health and sexual and reproductive health rights (as well as related language) in four of the key reports that fed into the process of negotiating the Sustainable Development Goals (SDGs). That process culminated in September 2015 with the United Nations (UN) General Assembly's adoption of the SDGs which include, in Goal 3, a commitment to 'Ensure healthy lives and promote well-being for all at all ages' and, in Goal 5 (' Achieve gender equality and empower all women and girls'), "universal access to sexual and reproductive health and reproductive rights. "…”
mentioning
confidence: 99%